Analisis Kinerja Keuangan Perbankan Di Bursa Efek Indonesia - Rizka Ariyanti; Iqbal N A; Adi Gunawan (Owner : Riset dan Jurnal Akuntansi, 2018)
This study aims to examine and analyze financial performance (ROA) and Return Shares (Studies in Bank Go Public in Indonesia Stock Exchange 2010-2014). To test these variables, the researchers use the 25 companies that went public in Indonesia Stock Exchange. This type of research is explanatory research. Tehknikpengumpulan data using documentary techniques. The data used in this research are secondary data from financial statements published by banking companies during 2010-2014. Furthermore, the data collected was analyzed quantitatively using multiple regrensi using Eviews program version 8.1 Silmultan The results showed that the variable asset structure, asset quality, capitalization, and size affect the financial performance (ROA). Silmutan research shows that the variable asset structure, asset quality, capitalization, and size does not affect the Stock Price. Indicate that the asset structure is not significant negative on financial performance (ROA) but no positive effect and no significant effect on stock Price, variable asset quality significantly negative on financial performance (ROA), but no significant effect on stock returns, variable capitalization significant positive effect on financial performance (ROA), but a significant effect on stock returns, variable size significantly influence financial kenerja (ROA), but no significant effect on stock returns. Then the variables of financial performance (ROA) had no significant effect on stock returns